Effects of Changes in Osmolarity on the Biological Activity of Human Normal Nucleus Pulposus Mesenchymal Stem Cells - Hua Zhang; Wei Li; YaoHong Wu; Shengquan Zhang; Jie Li; Letian Han; Haoyu Chen; Ziyu Wang; Cailiang Shen; Yinshun Zhang; Hui Tao (Hindawi Limited, 2022)
The expansion and maintenance of the NPMSC (nucleus pulposus mesenchymal stem cell) phenotype are considered as potential therapeutic tools for clinical applications in intervertebral disc tissue engineering and regenerative medicine. However, the harsh microenvironment within the intervertebral disc is the main limitation of its regeneration. The osmolarity of the intervertebral disc is higher than that of other tissues, which has an important influence on the biological characteristics of NPMSCs. In this study, we observed the effect of different osmolarities on the biological characteristics of human normal NPMSCs cultured in vitro and explored the role of osmolarity in intervertebral disc degeneration. Our data demonstrated that the change in osmotic pressure has an important effect on the biological activity of NPMSCs, and this effect may occur through the P16INK4A/Rb pathway. This study provides a theoretical basis for the future treatment of intervertebral disc degeneration.